Clinical ophthalmic oncology : Uveal tumors - Singh, Arun D.; Damato, Bertil (Springer Berlin Heidelberg, 2014)
Written by internationally renowned experts, Clinical Ophthalmic Oncology provides practical guidance and advice on the diagnosis and management of the complete range of ocular cancers. The book supplies all of the state-of-the-art knowledge required in order to identify these cancers early and to treat them as effectively as possible. Using the information provided, readers will be able to: Provide effective patient care using the latest knowledge on all aspects of ophthalmic oncology. Verify diagnostic conclusions based on comparison with numerous full-color clinical photographs from the authors' private collections, histopathologic microphotographs, imaging studies, and crisp illustrations. Locate required information quickly owing to the clinically focused and user-friendly format. This volume, devoted solely to uveal tumors, explains the various diagnostic and biopsy techniques that may be used and describes the therapeutic options of potential value for different types of tumor.